2012
DOI: 10.1108/00330331211204584
|View full text |Cite
|
Sign up to set email alerts
|

Indian institutional repositories: a study of user's perspective

Abstract: Purpose -The present study aims to investigate the experience, contribution and opinions of users of respective institutional repositories (IRs) developed in India. Design/methodology/approach -The survey method was used. The data collection tool was a web questionnaire, which was created with the help of software provided by surveymonkey.com Findings -It was observed that 85.94 percent of respondents (154) were aware of the IR facility/service and 14.05 percent (26) were not aware of IR. More than half of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…It needs creative intervention from the authorities. In contrast to previous studies in India and abroad 20,24,39,26 , which pointed out preservation as one of the leading advantages of an IR, accessibility of work was highlighted by the majority of faculty members in CUSAT. Dissemination and preservation are the primary goals of an IR.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…It needs creative intervention from the authorities. In contrast to previous studies in India and abroad 20,24,39,26 , which pointed out preservation as one of the leading advantages of an IR, accessibility of work was highlighted by the majority of faculty members in CUSAT. Dissemination and preservation are the primary goals of an IR.…”
Section: Discussioncontrasting
confidence: 83%
“…Sawant 24 found that the majority of users were aware of IRs and were willing to contribute to IR. However, their self-archiving experience in IR was low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These include overviews (Bluh and Hepfer, 2013;Buehler, 2013), as well as case studies of individual institutions' experience, such as Imperial College London (Afshari and Jones, 2013), Ljubljana (Koler-Povh et al, 2014), Ohio SU (Connell, 2011) and Rochester (Bell and Sarr, 2010). There are also numerous country-specific studies, including Bangladesh (Hossam Haider Chowdhury et al, 2011;Islam and Akter, 2013;Mukhlesur Rahman and Mezbah-ul-Islam, 2014), India (Balaji Babu et al, 2012;Sawant, 2011Sawant, , 2012, Indonesia (Farida et al, 2015), Korea (Shin, 2010), Nigeria (Igwe, 2014), Spain (Rodríguez-Armentia and Amat, 2010), Thailand (Wipawin and Wanna, 2014), Sweden (Andersson and Svensson, 2013), USA (Nykanen, 2011covering small institutions) and Zimbabwe (Nyambi and Maynard, 2012). In addition, there are a number of regional studies, including the Arabian Gulf (Sajjad Ahmed and Al-Baridi, 2012), Europe (Peters and Lossau, 2011), Asia (Abrizah et al, 2010;Nazim and Mukherjee, 2011), and developing countries ( Jain, 2011).…”
Section: Repositoriesmentioning
confidence: 99%
“…Countries occurring in the VOSviewer analysis include Australia, China, Germany and India as well as the USA and it is apparent that approaches to OA policy and take-up have varied across these and other countries. The OA literature includes a large number of country-specific studies, including those from China (Cheng et al, 2012;Hu et al, 2013;Shao et al, 2013;Zhao and Wu, 2014) and India (Balaji Babu et al, 2012;Gutam et al, 2010;Mukherjee, 2014;Sahu and Arya, 2013;Sawant, 2011Sawant, , 2012Sawant, , 2013 providing studies of research attitudes and overviews of service implementations. It is interesting that these BRIC countries are particularly covered in the literature on OA since they are making an increasingly important contribution to academic research and communication in general (Elsevier, 2013).…”
mentioning
confidence: 99%
“…Reasons for setting up repositories vary from one institution of higher learning to another and that wide range of projected benefits has been suggested (Sawant, 2012). Academic libraries benefit from being involved in IR initiatives, and there are implications for scholarly communication.…”
Section: Rationale For Irsmentioning
confidence: 99%